A Multiconstrained QoS Aware MAC Protocol for Cluster-Based Cognitive Radio Sensor Networks. (7th May 2015) - Pritom, Mir Mehedi Ahsan; Sarker, Sujan; Razzaque, Md. Abdur; Hassan, Mohammad Mehedi; Hossain, M. Anwar; Alelaiwi, Abdulhameed
Traditional wireless sensor networks (WSNs) work over the unlicensed spectrum, and as the spectrum becomes increasingly crowded, they suffer from uncontrolled interference. Recently, cognitive radio based sensor networks (CRSNs) have been envisioned as a promising type of implementation that provides quality-of-service (QoS) features for data transmissions. However, key challenges remain in designing energy-efficient medium access control techniques that can achieve QoS. In this paper, we have developed a multiconstrained QoS aware MAC protocol, MQ-MAC, for a cluster based CRSN. In MQ-MAC, a data channel and a backup channel are assigned to a secondary user by the respective cluster head by using dynamic channel priorities. The user device can switch to the backup channel when a primary user appears to be operating over the data channel. Member nodes of a cluster are also prioritized with respect to the urgency of their generated data packets. Performance evaluations, carried out in NS-3 simulator, show that the proposed MQ-MAC protocol offers better performance than existing MAC protocols for CRSN.